2014
DOI: 10.1016/j.ihj.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PUFA on patients with hypertension: A hospital based study

Abstract: Findings of the study suggest that omega-3 PUFA dietary supplements augment the benefits of pharmacotherapy in hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
1
8
1
1
Order By: Relevance
“…Similar to other studies, our study found a higher sodium intake with higher plasma hsCRP (38) and a higher intake of PUFAs was associated with lower SBP (39). In contrast with these individual AHEI-2010 components, the overall AHEI-2010 was not significantly associated with CVD biomarkers.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to other studies, our study found a higher sodium intake with higher plasma hsCRP (38) and a higher intake of PUFAs was associated with lower SBP (39). In contrast with these individual AHEI-2010 components, the overall AHEI-2010 was not significantly associated with CVD biomarkers.…”
Section: Discussionsupporting
confidence: 88%
“…A placebo‐controlled observational study conducted in 2012 on 100 hypertensive subjects sought to determine the effects of omega‐3 PUFA supplementation on the blood pressure of hypertensive patients. The study also determined whether male and female hypertensive patients respond differently to PUFAs.…”
Section: Clinical Studies Of Omega‐3 Fatty Acids and Blood Pressurementioning
confidence: 99%
“…A few mechanisms can be proposed for the observed effect of sesame. A variety of studies suggested that sesamin possesses a notable capacity to enhance antioxidant activity . The antihypertensive effect of sesame, which is demonstrated by experimental studies, can be partly attributed to its antioxidant activities .…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research indicates that specific dietary constituents rich in polyunsaturated fatty acids (PUFA) and vitamin E may have protective effects on HTN and CVD. Sesame ( Sesamum indicum ) seeds are rich sources of vitamin E and PUFA with the potential to increase the antioxidant pool of the body, promote anti‐inflammatory properties and reduce blood pressure (BP) .…”
Section: Introductionmentioning
confidence: 99%